Sabbatical leave report: Fall 2014 - Cardone, Resha (2014)
Cardone wrote chapters of a book manuscript and submitted two related articles to peer reviewed journals. She also transcribed and edited a scholarly interview, presented portions of book project at conference and traveled to site of book topic for on-ground research. Accomplishments are different than outlined in original proposal. The report describes project issues and results. Book title is "Unbound and underground: Chile's Ergo Sun Project from the dictatorship to the digital era."
Keywords: dept.wll; faculty_collection; sabbatical_report

Unbound and Underground: Chile's Ergo Sun Project from the Dictatorship to the Digital Era - Cardone, Resha (2014)
Cardone wrote chapters of a book manuscript and submitted two related articles to peer reviewed journals. She also transcribed and edited a scholarly interview, presented portions of book project at conference and traveled to site of book topic for on-ground research. Accomplishments are different than outlined in original proposal. The report describes project issues and results.
Keywords: dept.wll; faculty_collection; sabbatical_report

Book Review: The labor of literature: democracy and literary culture in modern Chile. by Jane D. Griffin. Amherst and Boston: U of Massachusetts p, 2016, p. 218, 25.95/85.00. - Cardone, Resha Sophia (The Latin Americanist, 2017)
Keywords: book.review; dept.wll

María Elena Gertner: Conversación en torno a la literatura - Cardone, Resha Sophia (Revista Chilena De Literatura, 2016)
Keywords: dept.wll

The bachelet government: conflict and consensus in Post‐Pinochet chile edited by silvia borzutzky and gregory b. weeks - Cardone, Resha Sophia (The Latin Americanist, 2011)
Keywords: dept.wll; peer-reviewed

Book Review: Art beyond itself: anthropology for a society without a story line. by néstor garcía canclini. trans. david frye. durham: duke university press, 2014, p. 201, 23.95. - Cardone, Resha Sophia (The Latin Americanist, 2015)
Keywords: book.review; dept.wll

Nona fernández's mapocho: spirits in a material wasteland - Cardone, Resha Sophia (Studies in Twentieth-and Twenty-First Century Literature, 2015)
Keywords: dept.wll

The memory of state terrorism in the southern cone: argentina, chile, and uruguay. by FrancescaLessa and VincentDruliolle (eds.). new york: palgrave macmillan, 2011. p. 227, 85.00. - Cardone, Resha Sophia (The Latin Americanist, 2013)
Keywords: dept.wll; peer-reviewed

A remecer consciencia en Chile y en el extranjero: una conversación con Pía Barros sobre las antologías ¡Basta! - Cardone, Resha Sophia (A Contracorriente: Revista de Historia Social y Literatura en América Latina, 2013)
Keywords: dept.wll; ⛔ No DOI found

The Minor Tone of Desire - Barros, Pía; Cardone, Resha (Ediciones Sherezade, 2018)
Keywords: 21st century; Chilean fiction; Translations into English; Translations into English; Chilean fiction; Women authors; dept.wll; faculty_collection